Integrating active learning in a college speaking class - Pryla Rochmahwati (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2013)
Active learning strategies provide a wide variety of activities which can be integrated in a College EFL Class especially on Speaking 1 Course at Ponorogo Islamic State College. They provide many benefits, such as giving the students’ chances to apply various ways in order to comprehend the material. Also, they emphasize the significance of the learner’s involvement in the learning process. Active Learning strategies are considered appropriate to give students the same amount of chance in practicing their speaking skill and to pay attention in creating a learning situation. Some active learning strategies including the advantages and their application procedures are intended to help learners achieve the objective of Speaking1 course are presented in the article. Lecturers may, however, find that some just do not fit their style of teaching or that others would work well in their speaking class or with modifications. On the other hand, there are some obstacles that occur during theimplementation of active learning, namely disinterested students and time pressures.